FAKTOR-FAKTOR YANG EMPENGARUHI HASIL PRODUKSI TEMPE PADA SENTRA INDUSTRI TEMPE DI KECAMATAN SUKOREJO KABUPATEN KENDAL - Devia Setiawati (Economics Development Analysis Journal, 2013)
Soybean largest industrial centers in Kendal is located in District Sukorejo. However, soybean production is likely to remain at center. The purpose of this study is to investigate and analyze: (1) The state of production in industrial centers soybeans in District Sukorejo Kendal tend to decrease and not increase significantly? (2) Effect of capital, labor, raw materials for the production of soybean in District Sukorejo Kendal jointly or partially?The collected data were analyzed with descriptive analysis and the percentage of regression method. The results showed that: (1) production of soybean in the soybean industry centers in District Sukorejo Kendal tends to remain due to the fluctuating price of soybean so that employers can not increase its production capacity. (2) Put together capital variables (X_1), labor (X_2) and raw materials (X_3) a significant effect on the dependent variable yield. Partially capital and labor variables no significant effect on soybean yield while the raw material to yield significant perpengaruh prosuksi soybean soybean on industrial centers in the District Sukorejo Kendal.It can be concluded that the independent variables affect the dependent variable by 88.7% than that of soybean price fluctuations can affect the production capacity in the industrial centers tempe tempe in District Sukorejo Kendal. For the soybean industry business owners should also seek to develop this industry by finding and opening new marketing channels for increase soybean production quantities